A Case of Multiple Posterior Intercostal Artery Common Trunks in Conjunction with Additional Arterial Variations. (18th November 2021) - Fanselow, Nicholas R.; Wallace, Nolan; Sehi, Daniel; Coomar, Lokesh; Martin, John; Tan, Yun; Daly, Daniel T.
Abstract : Several thoracic vasculature variations were observed in an 81-year-old male cadaver during routine dissection. These included 5 common trunks of posterior intercostal arteries, a descending branch of the right vertebral artery, and atypical neurovascular relationships within intercostal spaces. On the right side, two common trunks of posterior intercostal arteries were observed supplying the 4th-7th intercostal spaces and 9th-11th intercostal spaces, respectively. There was also a small accessary branch supplying the 9th intercostal space. The first three posterior intercostal spaces on the right were supplied by a descending branch of the vertebral artery. On the left side, three common trunks of posterior intercostal arteries were encountered, supplying intercostal spaces 3-5, 6-7, and 11 plus the subcostal space. An atypical neurovascular relationship was observed in the right 6th intercostal space, as well as the left 2nd, 3rd, and 6th intercostal spaces. This is the first case report that presents 5 common trunks of posterior intercostal arteries, as well as common trunks in conjunction with other arterial variation in the posterior thoracic wall. These variations carry a high level of clinical significance and may be helpful in guiding decision-making related to surgical procedures related to the posterior thoracic cavity and spine.